Common or multiple futures for end of life care around the world? Ideas from the 'waiting room of history'. (January 2017) - Zaman, Shahaduz; Inbadas, Hamilton; Whitelaw, Alexander; Clark, David
Abstract: Around the world there is growing interest in the manner in which care is delivered to people at the end of life. However, there is little unanimity on what constitutes a 'good death' and the appropriate societal responses to the issue of delivering culturally relevant and sustainable forms of end of life care in different settings are not subjects of broad agreement. In this critical conceptual paper we focus on the emerging narratives of global palliative care and offer an assessment of their implications. We relate this to calls to improve end of life care across jurisdictions and settings, attempts to map and grade the development of palliative care provision, and to the emergence of a widely recognised global 'quality of death index'. We consider an alternative approach to framing this debate, drawn from a subaltern and post-colonial studies perspective and suggest that adopting a truly global perspective will require acceptance of the plurality of past and present local problems and issues relating to end of life care, as well as the plural possibilities of how they might be overcome. In that context, we would not aim to universalise or privilege one particular global future for end of life care. Instead of homogenising end of life interventions, we seek to be open to multiple futures for the care of the dying. Highlights: Post-colonial perspective re-frames debate on the future of global palliative care. Provides innovative critique of global rankings of 'quality of death'. Advocates multiple futures for end of life care in different settings. Applies much needed theoretical approach to debates on global end of life care.